PRAGMATIC OPTIONS OF THE DIALOGICAL TEXT AS A LANGUAGE UNIT - Nadezhda N. Shpilnaya (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie, 2021)
The purpose of the article is to analyse pragmatic variants of a dialogical text as a language unit. It is assumed that the pragmatic context of the dialogical text (dialogue) actualizing is associated with either informative or phatic intentions. Informative and phatic dialogues appear as pragmatic allotext of a dialogical text. The research methodology is based on the synthesis of derivational and anthropocentric language theories. The process of creating a dialogical text is considered, on the one hand, as a derivational process due to the suppositional relationship between the lexeme and the text, and on the other hand, as a process of interpreting the text in the pragmatic context of its actualization. The material for the study was the recording of oral and written speech of regular native speakers in an informal communication situation. The total number of analyzed speech patterns was 140 dialogic texts – 70 texts of each communication type. It is stated that the pragmatic actualization of the dialogical text is associated with the realization of paradigmatic and syntagmatic connections of lexemes. It is revealed that the syntagmatic model of a dialogical text genesis in informative communication is an adjoining model. A paradigmatic model of dialogic text genesis in informative communication is synonymy. In phatic communication, an attachment model was identified as a syntagmatic model of the genesis of a dialogical text. The paradigmatic model for the production of dialogic text in phatic communication is a homonym model.